LOCAL ORDER OF THE TRANSITION METALS FOR THE SUBSTITUTION COPPER-ALUMINUM-LAYERED DOUBLE HYDROXIDE-LIKE PHASE - Leroux F.; Moujahid E.M.; Roussel H.; Flank A.-M.; Briots V.; Besse J.-P. (My University, 2002)
The substitution in layered double hydroxide-like phases (LDH) of composition (Co2+1-y Cu2+y)2Al3+(OH)6Cl · n H2O (0 y 1) was studied by X-ray diffraction and X-ray absorption spectroscopy. It was found that the lamellar character is maintained over the entire range of the substitution. The local order for the composition {Co2Al} is typical of brucite-like sheets, whereas segregation into small domains may explain the results obtained when the percentage of Cu atoms is increased. The {Cu2Al} end-member material presents a local order around the Cu atoms closely related to the botallackite structure as present in basic layered Cu salts, with the presence of two distinct Cu Cu distances.
Keywords: Botallackite Structure; Layered Double Hydroxide; X-ray Absorption Spectroscopy